Menstrual Phenotypes in Relation to Insulin Resistance in Infertile Women with Polycystic Ovary Syndrome (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objective: To explore the menstrual phenotypes associated with endocrine, metabolic characteristics of infertile women with polycystic ovary syndrome.Materials and methods : The cross sectional study was carried out among 125 infertile women with polycystic ovary syndrome attending Infertility wing of the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2017 to December 2017. The women were evaluated by clinical history, examination, transvaginal sonogram and for endocrine and metabolic parameters. The women were divided into 5 groups according to their menstrual phenotypes: i) cycle length 21-35 days ii) oligomenorrhoea or cycle length > 35 days but less than 6 months iii) secondary amenorrhoea or cycle length ³6 months iv) polymenorrhoea or cycle length 35 days but less than 6 months (n=70) iii) secondary amenorrhoea or cycle length ³6 months (n=35) iv) polymenorrhoea or cycle length